The Trial of Henry Hetherington, on an Indictment for Blasphemy - Hetherington, H. (Henry), 1792-1849 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Trial of Henry Hetherington, on an Indictment for Blasphemy" by Henry Hetherington is a historical account written in the early 19th century. The work provides a detailed report of Hetherington's trial for blasphemy, a legal confrontation centered around his publication criticizing the Old Testament and the institutions it represents. The book situates Hetherington as a central figure who defends his right to free inquiry and expression against the backdrop of legal and societal norms that seek to suppress dissenting views. The opening portion of the work sets the stage for the trial, detailing the charges brought against Hetherington for selling a series of letters that challenge the teachings of the clergy and the authenticity of the Scriptures, particularly the Old Testament. It includes the formal indictment and key arguments presented by both the prosecution and defense, highlighting Hetherington's stance on the importance of free thought and inquiry in religion. He argues against the prosecution's claims of blasphemy, asserting that his criticisms are rooted in a quest for truth rather than an attempt to insult or vilify. This initial depiction of a trial not only introduces the historical context but also engages with broader themes of freedom of speech and the conflict between religion and reason. (This is an automatically generated summary.)
Release date is 2012-03-05
Produced by David Widger
Keywords: Hetherington, H. (Henry), 1792-1849 -- Trials, litigation, etc; Trials (Blasphemy) -- England -- London